Are adverse events in newly trained home dialysis patients related to learning styles? A single-centre retrospective study from Toronto, Canada. Issue 1 (20th January 2020) - Auguste, Bourne Lewis; Girsberger, Michael; Kennedy, Claire; Srithongkul, Thatsaphan; McGrath-Chong, Margaret; Bargman, Joanne; Chan, Christopher T
Abstract : Objectives: Home haemodialysis (HD) and peritoneal dialysis (PD) have seen growth in utilisation around the globe over the last few years. However, home dialysis, with its attendant technical complexity and risk of adverse events continues to pose challenges for wider adoption. We examined whether differences in patients' learning styles are associated with differing risk of adverse events in both home HD and PD patients. Design: Retrospective cohort study. Setting: Tertiary care hospital in Toronto, Ontario, Canada. Participants: One hundred and eighteen prevalent adult (≥18 years) home dialysis patients (40 PD and 78 home HD) were enrolled. Patients on home dialysis for less than 6 months or receiving home nursing assistance for dialysis were excluded from the study. Interventions: Enrolled patients completed (VARK) Visual, Aural, Reading-writing and Kinesthetic questionnaires to determine learning styles. Primary and secondary outcome measures: Home HD and PD adverse events were identified within 6 months of completing home dialysis training. Event rates were then stratified and compared according to learning styles. Results: Thirty patients had a total of 53 adverse events. We used logistic regression analysis to determine unadjusted and adjusted ORs for a single adverse event. Non-visual learners were 4.35 times more likely to have an adverse event (p=0.001). After adjusting for age, gender, dialysis modality, training duration, dialysis vintage, prior renal replacement therapy, visual impairment, education and literacy, an adverse event was still four times more likely among non-visual learners compared to visual learners (p=0.008). A subgroup analysis of home HD patients showed adverse events were more likely among non-visual learners (OR 11.1; p=0.003), whereas PD patients showed a trend for more adverse events in non-visual learners (OR: 1.60; p=0.694). Conclusions: Different learning styles in home dialysis patients exist. Visual learning styles are associated with fewer adverse events in home dialysis patients within the first 6 months of completing training. Individualisation of home dialysis training by learning style is warranted.